The applicant non-verbal behavior facing recruitment interviews - Pinto, Alberto Peixoto; Sousa, Cristina de (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
An interview is defined as a quality of meetings, face to face, in which, at the same time we pay attention both to the content of verbal and non verbal behavior. In the case of the selection interview (also known as job interview) we are in the presence of the most used instrument assess in the recruitment context and a very popular topic for researchers from nearly 100 years ago (Macan, 2009). In the last half-dozen years have emerged more than a hundred articles in newspapers and books on the subject (Posthuma, Morgeson & Campion, 2002) reporting research in three areas: structuring the script and validity (1), which indicators are measured (2) and which factors on the part of interviewee and interviewer can influence the outcome (3) (Macan, 2009). In the factors that can influence the outcome, the nonverbal behavior of interviewee is an important contribution to judgment decision of interviewer’s (favorable or not favorable) (Gifford, Ng, & Wilkinson, 1985).Nonverbal behavior includes a number of aspects of body language including facial expression, eye contact, posture, gesture and inter-personal distance (Mehrabian, 1972). This type of communication is in effect a series of cues that are encoded by the sender, either consciously or unconsciously and subsequently decoded by the receiver (Gabbott & Hogg, 2000). Each component of nonverbal behavior affects the interpersonal relationship in a different way. Furthermore, during a job interview, as in most of the social interaction scenarios, people in a conscious way tend to control more the verbal behavior stream than the nonverbal one (DePaulo, 1992) and since this last is more difficult to control and consequently to fake (Weisbuch, Ambady, Clarke, Achor, & Weele, 2010) the interviewer as an observer and decoder has more cues and with much more consistency to form and manage an impression about the interviewee. Therefore, there are a close relationship between the non-verbal behavior of the candidates and the impression management (IM) formed by interviewers. This concept aroused from the literature produced by organizational psychology and was adopted by selection interview research as being "an attempt conscious or unconscious to influence the image during the process of interaction" (Levashina & Campion, 2007, p. 1639). IM can be grouped into two categories: self-promotion and other enhancement. Both classifications - self-focused-type and other-focused-type tactics - have been adopted by many organizational researchers studying IM in job interviews (Erdogan, 2011). Self-promotion includes description on a positive way of past experience and accomplishments in order to create a good perception on the interviewer and, other enhancement, is related to flattering, opinion conformity, feigned helplessness and favor doing (Barrick, Shaffer, & DeGrassi, 2009). Candidates purposely train their control over the verbal behavior, meaning their verbal style of delivery and fluency, and also, the nonverbal actions such as smiling, making eye contact, nodding, leaning forward, and making hand gestures (Barrick et al., 2009). These variables (impression management, verbal and non verbal behavior), along with the physical attractiveness, are correlated with the interview rating (Goldberg & Cohen, 2004). Accordingly to Huffcutt (2011, p. 71) four studies were identified with relevant data: Burnett and Motowidlo (1998) found correlations between total structured interview ratings and independent assessments of nonverbal behaviors (gaze, smile, hand movement, and body orientation); Gifford and Wilkinson (1985) found correlations between interviewer ratings and independent ratings of nonverbal behaviors (dress, reclining angle, facial regard, smiling, and gestures); Lievens and Peeters (2008) found a correlation with the behavior description portion of their interview and the situational portion; finally, Tsai et al. (2005) found that self-reported use of friendly nonverbal cues like smiling and nodding are correlated with interviewer evaluations. All of these studies used verbal statements to refer non verbal behaviors considered by participants more relevant to the evaluations. However, It may be useful to traduce these verbal statements into non verbal codes in order to produce a categorization able to function as an orientation for selection interviewers. In all of the coding systems one of the most used is FACS (facial action coding system), developed initially in 1978 by Ekman & Friesen and revised in 2002 (Ekman, Friesen & Hager). It Includes 44 action units (AUs) which are the fundamental actions of individual muscles or groups of muscles and 14 action descriptors (ADs) or unitary movements that may involve the actions of several muscle groups. For most accurate annotation, FACS suggests agreement from at least two independent certified FACS encoders (Ekman & Friesen, 1978). Unlike systems that use emotion labels to describe expression, FACS itself is descriptive and includes no emotion-specified descriptors and so, explicitly, distinguishes between facial actions and inferences about what they mean. Also, because of its descriptive power, FACS is regarded by many as the standard measure for facial behavior and is used widely in diverse fields (Cohn & Ekman, 2005). Since the face was found to provide more information about the nature of the emotion than the intensity of the emotional state, it’s became important to observe body acts and still positions to understand that last point. Five categories of non verbal behavior were proposed by Ekman & Friesen (1969) as a coding system to decipher that emotional intensity: Emblems (1) are non verbal acts which have a verbal direct translation known by all members of a group, class or culture. Illustrators (2) are movements directly linked to the speech and serve to illustrate what is being said verbally. Affect Displays (3) are movements involving face or body or body parts (arms, hands) associated with the demonstration of primary affects. Regulators (4) are acts which aim to maintain and regulate the natural feedback regarding both speaking and listening postures. Adaptors (5) are those movements that were first learned to satisfy different development needs and after that became altered to respond to a certain demanding situation. We can distinguish between self, alter and object adaptors (Ekman & Friesen, 1969). Another factor that can influence the outcome of interview is the candidate motivation. There is very few data on the relationship between interview ratings and general work motivation and specifically between the motivation and the nonverbal behavior performed by the candidate in the interview. Accordingly to suggestions of Huffcutt (2011) about the importance of assess the influence on interview ratings, in our study we plan to search for correlations between job interview ratings, nonverbal behavior and the three motivators of McClelland’s Motivation Theory: achievement, affiliation, power (Rego, 2000). The employment interview is a context where a variety of constructs are measured, including personality traits. Interviewers tend to make assessments of interviewee personality traits which influence their evaluations of applicant capacities. Big Five Personality attributions can be a good mediator between the nonverbal cues and the interview performance rating (DeGroot & Gooty, 2009). Our objective, taking in account all the above information, is to analyze the relation between the non verbal behaviors of the candidate in a real selection interview context and the decision-making of the interviewer. For that, we intend to identify specific nonverbal behaviors of candidates in real selection procedures that contribute to judgment decision of interviewer’s (favorable or not favorable) and, on the other hand, we also intend to analyze if the evaluation of some specific facial expressions and gestures are related with the self-evaluation of another characteristics (Personality and Motivation).